2021
DOI: 10.1007/s40265-021-01558-2
|View full text |Cite|
|
Sign up to set email alerts
|

Netupitant/Palonosetron: A Review in Chemotherapy-Induced Nausea and Vomiting

Abstract: Netupitant/palonosetron (NEPA; Akynzeo ® ), available in oral and intravenous (IV) formulations, is a fixed-dose combination of the neurokinin 1 (NK1) receptor antagonist netupitant (or the prodrug, fosnetupitant, in the IV formulation) and the second-generation serotonin 3 (5-HT 3 ) receptor antagonist palonosetron. Administered as a single dose, (fos)netupitant/palonosetron (in combination with dexamethasone) is indicated for the prevention of acute and delayed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Consistent with previous research resultss, the acute phase is mainly mediated by 5-HT 3 receptors and is therefore particularly sensitive to 5-HT 3 receptor antagonists [16].In our study, acute CINV can be effectively controlled by the use of panolosetron, which has a high a nity for binding to 5-HT3 receptors. Panolosetron also inhibits cross-talk between the NK-1 and 5-HT3 receptor pathways [17], which is assumed to be the cause of the observed effect in preventing delayed nausea and vomiting. As a result, our ndings revealed that panolosetron and fosaprepitant act synergistically to keep the overall incidence of nausea (≤12%) and vomiting (≤4%) at a low level.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous research resultss, the acute phase is mainly mediated by 5-HT 3 receptors and is therefore particularly sensitive to 5-HT 3 receptor antagonists [16].In our study, acute CINV can be effectively controlled by the use of panolosetron, which has a high a nity for binding to 5-HT3 receptors. Panolosetron also inhibits cross-talk between the NK-1 and 5-HT3 receptor pathways [17], which is assumed to be the cause of the observed effect in preventing delayed nausea and vomiting. As a result, our ndings revealed that panolosetron and fosaprepitant act synergistically to keep the overall incidence of nausea (≤12%) and vomiting (≤4%) at a low level.…”
Section: Discussionmentioning
confidence: 99%
“…Fosnetupitant is a novel NK 1 receptor antagonist for intravenous administration, which has high selectivity and affinity for NK 1 receptors [ 20 , 21 ].…”
Section: Mechanism Of Action Of Fosnetupitantmentioning
confidence: 99%
“…[ 1 ] To date, more than ten oligonucleotide therapeutics have been approved by the US Food and Drug Administration (FDA); most are antisense oligonucleotide and short interfering RNA (siRNA) drugs. [ 1b,2 ] The considerable therapeutic effects and broad room for improvement continue to inspire further exploration. The research challenge remains the delivery efficiency of targeted oligonucleotides and includes impermeability to cells, nuclease degradation, and failed lysosome escape.…”
Section: Introductionmentioning
confidence: 99%